Aprendizagem mobilizada por questões sóciocientificas : uma ação formativa interdisciplinar com docentes de Ciências Naturais - Vilas Boas, Terezinha de Jesus Reis (2020)
This work aimed to understand the contributions for teaching with socio-scientific issues. The study presents as a research question: what contributions of work with socio-scientific issues, in a formative action, would provide in relation to the learning of environmental knowledge into a critical scientific perspective, for Natural Sciences teachers. This research was developed during a 40-hour interdisciplinary training action, with 30 Science teachers, where the theme precipitation and temperature was discussed and studied in the municipality of Presidente Figueiredo, Amazonas; a subject that is part of an experiential reality of the teachers involved in it. Studies about teacher training, in particular, the teachers training of Natural Science, knowledge for teaching and socio-scientific issues have contributed for construction of the theoretical references and have served as guides for analyzes. Thirty Science teachers, in service for the Education Department of Amazonas State and for the Education Department of Presidente Figueiredo have participated of activites. Newspaper news, videos from the internet, scientific articles and scientific dissemination were used in this interdisciplinary training action, in order to presente different actors and understandings on the subject, precipitation and temperature. The following instruments were used for data collection: questionnaire, semistructured interview, reflective diary, matrices, audio and video recordings. Content Analysis (CA) was researched from the records, in order to constitute the corpus of the analysis and proceed with the elaboration to comprehend the phenomenon. In the data analysis, aspects to be considered were established from the goals and research essues according to the categories of knowledge for teaching explored in it: knowledge of contente, didactic-pedagogical knowledge and critical knowledge. The analyzes were carried out, paying attention to the contribution of knowledge learning with QSCs, aiming at a training based on an interdisciplinary and critical perspective. Thus, the ideas for overcoming the individualism of the subject are explicit, the perception of the need for a more interdisciplinary teaching action, valuing everyday themes and citizen action in society to promote changes, ideas that emerge from the formative pretensions for the Natural Science teachers and the theoretical references used. The results show that a formative action involving the analysis of socio-scientific issues brings subsidies of reflection for possibilities that mobilize knowledge for Science teachers in service, in interdisciplinary and critical perspective. Furthermore, it has got possible to identify the weaknesses and challenges in relation to activities with QSC approach, which in essence, are imterdisciplinary and that need to be considered and overcome.